2008
DOI: 10.1890/07-0774.1
|View full text |Cite
|
Sign up to set email alerts
|

Longevity Can Buffer Plant and Animal Populations Against Changing Climatic Variability

Abstract: Abstract. Both means and year-to-year variances of climate variables such as temperature and precipitation are predicted to change. However, the potential impact of changing climatic variability on the fate of populations has been largely unexamined. We analyzed multiyear demographic data for 36 plant and animal species with a broad range of life histories and types of environment to ask how sensitive their long-term stochastic population growth rates are likely to be to changes in the means and standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
482
7
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(552 citation statements)
references
References 28 publications
(33 reference statements)
41
482
7
3
Order By: Relevance
“…Our study contributes two notable exceptions to the accepted view that short-lived species, regardless of habitat, are particularly vulnerable to climate change [26]. We argue that for both species, the potential for demographic buffering is high, in the light of the resulting higher stochastic population growth rates.…”
Section: Climate Change Precipitation and Desert Plant Demographymentioning
confidence: 63%
See 1 more Smart Citation
“…Our study contributes two notable exceptions to the accepted view that short-lived species, regardless of habitat, are particularly vulnerable to climate change [26]. We argue that for both species, the potential for demographic buffering is high, in the light of the resulting higher stochastic population growth rates.…”
Section: Climate Change Precipitation and Desert Plant Demographymentioning
confidence: 63%
“…A meta-analysis using size-/stage-based demographic models concluded that species with short lifespans are more vulnerable to increased stochasticity than long-lived species [26]. Lewontin & Cohen [29] derived an approximation for the stochastic population growth rate (a ¼ log(l S )) that points to the negative effect of variation in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long lifespan of individual plants, as well as life-history traits such as clonal reproduction, tend to enhance population persistence (Eriksson 1996), and long-lived plants generally show more stable population dynamics than short-lived plants (García et al 2008;Silvertown et al 1993). Thus, negative effects of sub-optimal environmental conditions could be expected to be delayed (Morris et al 2008). Previous studies have found a strong positive effect on biomass of G. sylvaticum after protecting it from grazers in alpine snow beds (Moen and Oksanen 1998), but that the magnitude of the effect depends on habitat productivity (Olofsson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, longevity can play a role in how quickly growth rate in a population responds to climate change (Morris et al 2008). In their metaanalysis of demographic data for 36 plant and animal species, Morris et al (2008) found that the population growth rates of long-lived species were buffered from changes in rates of reproduction and survival relative to short-lived species. Thus, long-lived species may be better equipped to persist in an environment in which phenological mismatches become increasingly common.…”
Section: Recommendations For Future Research (A) Optimize Monitoring mentioning
confidence: 99%